Prototype Development of Mobile-Based Commodity Exchange Information Application for Indonesian Companies - Krizia Gidion Gaghana; Rudi Sutomo (Universitas Islam Raden Rahmat, Malang, 2023)
Commodity exchanges are marketplaces where various commodities, including metals, energy, agriculture, etc., are traded. Here, buyers, sellers, and investors can transact in spot contracts or items futures. According to literature reviews based on prior research, in-person contacts and encounters can strengthen professional ties, create a sense of trust, and provide a thorough understanding of client preferences and wants. Online commodity dealing may have this restriction because there may be little opportunity for in-person encounters. Mobile electronic communication technologies and media can diminish face-to-face human interaction while facilitating information access and sharing to solve this issue. A computer, laptop, or mobile device can be used to access this platform, which is an online trading system. Traders can view current commodity pricing information. A mobile-based application for Commodity Exchange Information that was created using Flutter technologies and the Extreme Programming approach is one of the most successful and effective methods of information dissemination. With powerful indicators and user needs, the User Acceptance Test (UAT) method and the Black-box testing model's final step of application testing yielded a score of 93.75%.